Ball Grid Array Module with Integrated Shaped Lens for 5G Backhaul/Fronthaul Communications in F-Band - Bisognin, A.; Nachabe, N.; Luxey, C.; Gianesello, F.; Gloria, D.; Costa, J.; Fernandes, C.; Alvarez, Y.; Arboleya, A.; Laviada, J.; Las-Heras, F.; Dolatsha, N.; et al. (IEEE Transactions on Antennas and Propagation, 2017)
In this paper, we propose a ball grid array (BGA) module with an integrated 3-D-printed plastic lens antenna for application in a dedicated 130 GHz OOK transceiver that targets the area of 5G backhaul/fronthaul systems. The main design goal was the full integration of a small footprint antenna with an energy-efficient transceiver. The antenna system must be compact and cost effective while delivering an approximately 30 dBi gain in the working band, defined as 120 to 140 GHz. Accordingly, a 2×2 array of aperture-coupled patch antennas was designed in the 7×7×0.362 mm3 BGA module as the feed antenna of the lens. This achieved a 7.8 dBi realized gain, broadside polarization purity above 20 dB, and over 55% total efficiency from 110 to 140 GHz (20% bandwidth). A plastic elliptical lens 40 mm in diameter and 42.3 mm in height was placed on top of the BGA module. The antenna achieved a return loss better than ?10 dB and a 28 dBi realized gain from 114 to 140 GHz. Finally, active measurements demonstrated a >12 Gbps Tx/Rx link at 5 m with bit error rate (BER) < 10?6 at 1.6 pJ/b/m. These results pave the way for future cost-effective, energy-efficient, high-data rate backhaul/fronthaul systems for 5G communications.